Mediation of pain in the association of sleep problems with falls among older adults in India - T. Muhammad; Priya Maurya; Y. Selvamani; Uma Kelekar (Scientific Reports, 2023)
Abstract Body pain, sleep problems and falls are commonly reported among the elderly population. This study aimed to explore the mediating role of pain in the association of sleep problems with fall-outcomes (falls, fall-injury, and multiple falls) among older adults. Cross-sectional data from the baseline survey of Longitudinal Aging Study in India (LASI), 2017–18 were used. The total sample size for the study was 28,285 older adults aged 60 years and above. Falls and fall-related injuries among older adults in the last two years were self-reported. The Jenkins Sleep Scale (JSS-4) was used to assess sleep problems while pain was assessed using questions on whether respondents reported that they were troubled by pain and they required some form of medication or treatment for the relief of pain. Multivariable logistic regression and mediation analyses were conducted to fulfill the study objectives. While 13% older adults suffered from sleep problems, 38.83% were troubled with pain. Additionally, 12.63%, 5.64% and 5.76% older adults reported falls, fall-injury and multiple falls respectively. Older adults who suffered from sleep problems had higher odds of falls [adjusted odds ratio (aOR): 1.43, confidence interval (CI): 1.30–1.58], fall-injuries, [aOR:1.50,CI:1.30–1.73] and multiple falls [aOR:1.41,CI:1.24–1.62]. Similarly, older adults who were troubled with pain were more likely to report falls [aOR:1.80, CI:1.67–1.95], fall-injuries [aOR:1.66, CI:1.48–1.87] and multiple falls [aOR:1.90,CI:1.69–2.12]. The percent of the mediated effect of pain when examining the association between sleep problems and fall outcomes were reported to be 17.10%, 13.56% and 18.78% in case of falls, fall-injuries and multiple falls respectively. The current study finds evidence that pain mediates the association of sleep problems and falls, fall-injuries, and multiple falls among older Indian adults. Both sleep problems and pain are modifiable risk factors that need attention for fall prevention strategies.